Trends in psychosomatic symptoms among adolescents and the role of lifestyle factors - Benti Geleta Buli; Susanna Lehtinen-Jacks; Peter Larm; Kent W. Nilsson; Charlotta Hellström-Olsson; Fabrizia Giannotta (BMC, 2024)
Abstract Background Adolescent mental health problems are on the rise globally, including in Sweden. One indicator of this trend is increased psychosomatic symptoms (PSS) over time. Lifestyle factors such as physical activity (PA), diet, smoking, and alcohol consumption may influence the time trends in PSS; however, the evidence base is scarce. The aim of this study was to investigate associations between time trends in PSS and lifestyle factors. Methods The study was based on data collected from a nationally representative sample of 9,196 fifteen-year-old boys and girls in Sweden using the Health Behavior in School-aged Children (HBSC) symptom checklist. The sample comprised nearly equal proportions of girls (50.5%) and boys. The lifestyle factors examined in this study included PA, regular breakfast intake, consumption of fruits, vegetables, sweets, or soft drinks, smoking, and alcohol drunkenness. We used data from 2002 to 2018 and stratified by family affluence scale (FAS) to demonstrate how the associations varied among the FAS groups. We fitted separate regression models for the high- and low-FAS groups, where interaction terms between the year of survey and each lifestyle factor were used to estimate the level and direction of associations between the factors and trends in PSS. Results There was a generally increasing trend in PSS mean scores from 2.26 in 2002 to 2.49 in 2018 (p <.001). The changes in each survey year compared to the average mean scores during the preceding years were significant in all years except 2010. Regular breakfast intake, daily fruit and vegetable consumption, and higher PA were associated with lower PSS mean scores, while smoking and drunkenness had opposite associations with PSS. The only significant interaction between survey year and the lifestyle factors was observed regarding drunkenness in the high FAS group, suggesting that the association between trends in PSS and the experience of getting drunk at least twice got stronger over time (B = 0.057; CI:0.016, 0.097; p <.01). Conclusions The results indicate increasing trends in PSS among young people in Sweden from 2002 to 2018, with a significant increase observed among adolescents in the high FAS group who reported getting drunk on at least two occasions.